Chinese spies use LinkedIn to target UK officials and military staff - Badshah, Nadeem (The Guardian, 2026)
Advertisements for non-existent jobs aim to draw in people with access to classified or sensitive information
United Kingdom
Keywords: China; Espionage; MI5; UK news; UK security and counter-terrorism; World news